PKM KELOMPOK TANI BAWANG MERAH “SEJAHTERA” DESA BALUNG GEBANG, KEC. GONDANG, KAB. NGANJUK, JAWA TIMUR - Setiani, Puspita Pebri; Khotimah, Khusnul (JPM Pambudi, 2018)
Bawang Merah Farmer Group "Sejahtera" is one of the brambang farmer groups in Balung Gebang village, Kec. Gondang Kab. Nganjuk, where Nganjuk is famous as the center of shallots in East Java with a total planting area of 11,300 ha, the second widest after Brebes. The shallot cultivation centers in Nganjuk Regency are in five subdistricts, namely Bagor, Wilangan, Sukomoro, Gondang, and Rejoso. The Purpose of PKM Bawang Merah Farmers Group "Sejahtera" Balung Gebang Village Kec. Gondang Kab. Nganjuk East Java is for the manufacture of farmers' drying plants to maintain the quality and quantity of shallots when the post-harvestprocess is due to the PKM partners having problems in the form of high-quality shallot products with low quality. The method used in this PKM as a solution to the problems of PKM partners is to conduct counseling on post-harvest handling of shallots in the "Sejahtera" shallot farmer group in the village of Balung Gebang, Gondang District, Nganjuk District, East Java. The results in this PKM are increasing the yield of dry shallots ready for sale with quality or dry as long as possible and minimizing the level of onion decay due to the postharvest drying system, namely by instore drying.